Brain and Human Body Modeling 2020 2020
DOI: 10.1007/978-3-030-45623-8_9
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturized Ultra-Focal Magnetic Stimulator and Its Preliminary Application to the Peripheral Nervous System

Abstract: Transcranial magnetic stimulation (TMS) is a noninvasive brain stimulation technique that employs a high-intensity pulsed magnetic field sent through the scalp by a stimulating coil. According to Faraday's law, a time-varying magnetic field induces inside the brain tissue an electric field, which may elicit a neuronal response. Due to the lack of physical contact, TMS results in almost a painless stimulation compared to electric noninvasive techniques, and for this reason, it has been deeply investigated over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For a good trade-off between overall coil height and the number of turns, the trace thickness was selected equal to 35 µm or 1 Oz., which allowed a single trace height of 1 mm with a 2.847 m in length and overall target resistance of 1.4 Ω. Supported by previous FEM numerical simulations, [75][76][77] we fabricated the mcoil as four copper micro traces (four-layered) etched using photolithography on a polyimide substrate (Figure 1). The overall height of the mcoil was only 5.1 mm, given the trace-to-trace spacing of just 0.38 mm (Figure 3a).…”
Section: The Mcoil Fabrication and The F-nims Driving Systemmentioning
confidence: 99%
“…For a good trade-off between overall coil height and the number of turns, the trace thickness was selected equal to 35 µm or 1 Oz., which allowed a single trace height of 1 mm with a 2.847 m in length and overall target resistance of 1.4 Ω. Supported by previous FEM numerical simulations, [75][76][77] we fabricated the mcoil as four copper micro traces (four-layered) etched using photolithography on a polyimide substrate (Figure 1). The overall height of the mcoil was only 5.1 mm, given the trace-to-trace spacing of just 0.38 mm (Figure 3a).…”
Section: The Mcoil Fabrication and The F-nims Driving Systemmentioning
confidence: 99%
“…Previous 3-D FEM approaches have either used idealized geometries such as a cylindrical arm [44][45][46] or derived from 2-D anatomical images by extruding geometry [35] and limiting to certain cross sections [32]. The modeling methodology applied here, from the geometry, applying EM simulations into a dynamic Neuron solver, using the MRG model, and subsequently using titration analysis, mimics the one employed in the context of magnetic stimulation (MS) [22]. The simulation setup used in the aforementioned MS study has been further validated using clinical experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A recent work simulated the micro-coil stimulation of the radial nerve fibers in arms with a circular micro-coil and a figure-eight micro-coil. The authors found that the threshold current in the figure-eight micro-coil was significantly less than the circular micro-coil for neural activation ( Colella et al, 2021 ). Our results are generally in agreeance with this report.…”
Section: Discussionmentioning
confidence: 99%
“…Saito constructed a figure-eight micro-coil using commercially available chip inductors, which effectively suppressed synchronized bursting activity in a cultured neural network ( Saito, 2021 ). Colella et al (2021) simulated axonal stimulation of peripheral nerves with the figure-eight micro-coil, and found that the threshold for axonal activation was lower for the figure-eight coil than for a circular micro-coil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation